Disuguaglianza di reddito e di ricchezza in Italia dalla Grande Guerra alla crisi del 2008. Un inquadramento generale - Raspadori, Paolo (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
The paper focuses on income and wealth trends in Italy from the outbreak of World War I to the Great Recession of 2008. Drawing on international datasets available online, data collected by distinguished scholars on the subject, and other information contained in reports on wealth and wages, the evolution of the main indicators of economic inequality in our country (Gini coefficient, Theil index, percentage shares of income reported to the tax authorities, etc.) is reconstructed. What emerges from the analysis is a crystallization of current income and wealth disparities from the outbreak of World War I to the end of World War II, a sharp decline from the 1950s to the 1980s, and a resurgence from the 1990s to the 2010s.